Upaya Meningkatkan Hasil Belajar IPA pada Materi Perubahan Wujud Benda Melalui Metode Eksperimen SDN 054906 Tebasan Lama - Tri Dina Kandi; Tri Rahayu Saputri; Syahrial Syahrial (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2024)
The problem with the teaching methods used by teachers in the classroom in science subjects, especially the material "changes in the form of objects", is that teachers only use lecture or theory methods so that the learning process is only teacher-centred and has an impact on low student learning outcomes. The aim of this research is to make efforts to improve students' science learning outcomes through experimental methods at SDN 054906 Tebasan Lama. This type of research is Classroom Action Research (PTK). The subjects of this research were 20 class III students at SDN 054906 Tebasan Lama. This research data collection technique was carried out using tests and non-tests, the tests contained evaluation questions to measure learning outcomes and the non-tests consisted of observation and documentation observation sheets. The data analysis technique uses reflection analysis by connecting the data obtained through tests with predetermined success criteria data. The results of the research showed that before being given experimental method treatment in cycle I (pre-test) the learning outcomes were obtained with an average score of 48 and a completion percentage of 25% of the minimum completeness criteria, whereas after being given experimental method treatment in cycle II (post-test) There was an increase in the completion percentage by 60% with an average value of 82.75 and a completion percentage of 85%. So it can be concluded that efforts to improve students' science learning outcomes using experimental methods at SDN 054906 Tebasan Lama were declared successful and had a positive impact on improving student learning outcomes.